2018
DOI: 10.1111/petr.13125
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography for non‐invasive evaluation of post‐transplant liver graft fibrosis in children

Abstract: As graft survival in pediatric LT is often affected by progressive fibrosis, numerous centers carry out protocol liver biopsies. Follow-up biopsy protocols differ from center to center, but all biopsies are progressively spaced out, as time from transplant increases. Therefore, there is a need for non-invasive techniques to evaluate graft fibrosis progression in those children who have no clinical or serological signs of liver damage. Indirect markers, such as the APRI, should be relied on with caution because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 55 publications
(132 reference statements)
2
24
3
Order By: Relevance
“…We found a significant association between LSM and METAVIR fibrosis staging based on histological assessment of liver biopsies in pediatric liver transplant recipients. These results support and add to previously published data also showing a correlation between liver stiffness and hepatic fibrosis 13,14 . Our data conflict with a recent study which showed only a 66.7% accuracy of LSM in predicting fibrosis 20 .…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…We found a significant association between LSM and METAVIR fibrosis staging based on histological assessment of liver biopsies in pediatric liver transplant recipients. These results support and add to previously published data also showing a correlation between liver stiffness and hepatic fibrosis 13,14 . Our data conflict with a recent study which showed only a 66.7% accuracy of LSM in predicting fibrosis 20 .…”
Section: Discussionsupporting
confidence: 65%
“…Although VCTE was initially used in adults, it has since been shown to be feasible in children 10,11 . There are limited data regarding its use to predict hepatic fibrosis in pediatric post‐transplant patients, however, with the main limitations in these studies being small number of patients and lack of universal use of the S probe for smaller children 12‐15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its use in children who have received LT has been reported in only a few small studies. 15,[19][20][21] The aim of this study was to evaluate the ability of TE to predict clinically significant, histologically assessed liver graft fibrosis (METAVIR F2-F4) in a large cohort of pediatric and young adult LT recipients at a single transplant center. Secondary aims were (a) to compare the predictive ability of TE to that of the APRI and the FIB-4, and (b) to investigate whether or not graft type had any effect on the performance of LSMs.…”
Section: Introductionmentioning
confidence: 99%
“…as part of MV. At LSM, median ALT was 25 [IQR [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]] IU/L. Twenty-one percent had METAVIR ≥ F2.…”
mentioning
confidence: 99%